Knowledge, attitude and practice on screening and early diagnosis of prostate cancer of primary health care providers in the Free State - Matthew O.A. Benedict; Wilhelm J. Steinberg; Frederik M. Claassen; Nathaniel Mofolo; Cornel van Rooyen (AOSIS, 2023)
Background: Prostate cancer is topmost in terms of incidence and mortality among men in sub-Saharan Africa, including South Africa. Prostate cancer screening is beneficial only to certain categories of men, making a rational screening approach necessary. Aim: This study aimed to assess the knowledge, attitudes and practice (KAP) regarding prostate cancer screening among primary health care (PHC) providers in the Free State, South Africa. Setting: Selected district hospitals, local clinics and general practice rooms. Methods: This was a cross-sectional analytical survey. Participating nurses and community health workers (CHWs) were selected through stratified random sampling. All available medical doctors and clinical associates were approached to participate, totalling 548 participants. Relevant information was obtained from these PHC providers using self-administered questionnaires. Both descriptive and analytical statistics were computed using Statistical Analysis System (SAS) Version 9. A p-value 0.05 was considered significant. Results: Most participants had poor knowledge (64.8%), neutral attitudes (58.6%) and poor practice (40.0%). Female PHC providers, lower cadre nurses and CHWs had lower mean knowledge scores. Not participating in prostate cancer-related continuing medical education was associated with poor knowledge (p 0.001), negative attitudes (p = 0.047) and poor practice (p 0.001). Conclusion: This study established appreciable KAP gaps relating to prostate cancer screening among PHC providers. Identified gaps should be addressed through the preferred teaching and learning strategies suggested by the participants. Contribution: This study establishes the need to address KAP gaps regarding prostate cancer screening among PHC providers; therefore necessitating the capacity-building roles of district family physicians.